INFLUENCE OF MACROECONOMIC FACTORS ON THE GROWTH OF THE INSURANCE INDUSTRY - Kajwang, Ben (International Journal of Economics, 2022)
Purpose: The purpose of this study was to examine the influence of macroeconomic factors on the growth of insurance industry in Kenya. Materials and Methods: The main research approach used in this study relied on review of previous studies related to the study topic. This involves the use of secondary data obtained from institution records, government publications, historical and statistical records etc. This type of data is frequently chosen since it can be conveniently accessed and reduces the need for field research. Therefore, this study will rely heavily on already published studies, journals and annual records of insurance companies in Kenya to obtain secondary data that will be used to draw the results, conclusion and recommendations of the study. Findings: The findings from the empirical studies were found to have conceptual, contextual and geographical gaps. This is because most of these studies discussed on either internal factors or both internal and macroeconomic factors influencing the performance or profitability of insurance companies. The findings of these studies were also limited to a few measures of growth of insurance firms. In addition, most of the empirical studies were not carried out in Kenya. Hence, the findings of these studies may differ due to the different governing systems used by different countries that also affect the operations of insurance companies. Unique contribution to theory, practice and policy: This study will be of great benefit to the different stakeholders in the insurance sector in Kenya. The management of the insurance companies will gain a broad understanding of the numerous macroeconomic factors and how they impact the performance and profitability of insurance firms. The policymakers in the insurance industry will also benefit from the suggestions and recommendations given on measures and policies that can be used to reduce the adverse effects of macroeconomic factors on the growth of the insurance industry. The findings of the study can also be used as a reference point to identify the macroeconomic factors that have a positive influence and those with a negative influence on the development of the insurance industry. Further, this study will also be relevant to the different researchers and academicians since the study's findings will be incorporated into their body of literature and act as a basis for their empirical studies. On the other hand, the scholars may also be motivated to carry out additional research in order to improve on the theories used in this study and fill any identified research gaps.